2015
DOI: 10.1111/fcre.12128
|View full text |Cite|
|
Sign up to set email alerts
|

Reforming Relocation Law: An Evidence‐Based Approach

Abstract: In recent years, there has been much discussion within international fora about the need for a greater consensus on how to approach relocation cases. Empirical research on the lived experience of parents and children who have been through relocation disputes has an important role to play in providing an evidence base for decisions on policy. In this article, we summarize the findings of a 5-year prospective longitudinal study of relocation disputes in Australia and make recommendations in the light of this and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 35 publications
1
27
0
2
Order By: Relevance
“…Parkinson and Cashmore () present their findings from a qualitative, descriptive, and prospective study of parents who have been involved in child custody relocation disputes and their personal experiences in light of the judicial outcome. Parkinson and Cashmore report on the “voices” of parents and children as a result of their “relocation experience.” In this sense, the research is consistent with a phenomenological approach to research (Moustakas, ).…”
Section: Contrasting Methodologies On Relocation Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Parkinson and Cashmore () present their findings from a qualitative, descriptive, and prospective study of parents who have been involved in child custody relocation disputes and their personal experiences in light of the judicial outcome. Parkinson and Cashmore report on the “voices” of parents and children as a result of their “relocation experience.” In this sense, the research is consistent with a phenomenological approach to research (Moustakas, ).…”
Section: Contrasting Methodologies On Relocation Researchmentioning
confidence: 99%
“…Parkinson and Cashmore report on the “voices” of parents and children as a result of their “relocation experience.” In this sense, the research is consistent with a phenomenological approach to research (Moustakas, ). Parkinson and Cashmore () present their ideas and proposals for legal reform as “evidenced‐based” research. However, the qualitative nature of the research renders the research as not sufficiently scientific or reliable to be part of expert testimony.…”
Section: Contrasting Methodologies On Relocation Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…This research generally shows that relocation is a stronger predictor of childhood maladjustment that is more pronounced for children of divorce; therefore, it can be concluded that relocation is a general risk factor for children of divorce, just as divorce is itself (McLanahan & Sandefur 1994;Tucker, Marx, & Long, 1998). While relocation creates risks, longitudinal, international research suggests that most children of divorce who relocate show a satisfactory long-term adjustment to living in their new community, if protective factors, such as having a resourceful, custodial moving parent with an effective parenting style (Parkinson & Cashmore, 2015;Taylor & Freeman, 2010) are in place. While relocation creates risks, longitudinal, international research suggests that most children of divorce who relocate show a satisfactory long-term adjustment to living in their new community, if protective factors, such as having a resourceful, custodial moving parent with an effective parenting style (Parkinson & Cashmore, 2015;Taylor & Freeman, 2010) are in place.…”
Section: Prior Research Findingsmentioning
confidence: 99%